Social Capital, Financial Literacy, and Rural Household Entrepreneurship: A Mediating Effect Analysis - Zhao, Jingmei; Li, Tiancheng (Frontiers in Psychology, 2021)
In rural areas, entrepreneurship helps lift households out of poverty by alleviating unemployment and increasing income, and financial literacy plays an important role in promoting entrepreneurship. Social capital is a resource embedded in social relationships, the boundaries of which have been expanded by the development of information communications technologies (ICTs). This article aims to link social capital, financial literacy, and rural entrepreneurship through a partial mediating effect analysis. Using data from the 2015 China Household Finance Survey (CHFS), we analyze how social capital affects rural entrepreneurship and the role of local ICTs development in this effect while also accounting for reverse causality. We construct a social capital indicator, mainly referring to bridging social capital, and two financial literacy indicators to make the conclusions robust. The empirical results show that social capital promotes rural entrepreneurship by sharing financial literacy. Furthermore, the spread of ICTs enhances this mediating effect. Our study provides empirical evidence for encouraging entrepreneurship and promoting knowledge sharing and implies the importance of ICTs in promoting entrepreneurship in rural areas.